2021
DOI: 10.1371/journal.pone.0255482
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin D in subjective tinnitus—A case-control study

Abstract: Regarding the high prevalence of vitamin D (25(OH)D) deficiency in the population and its possible association with ear diseases, we aimed to investigate the 25(OH)Dserum level in patients with subjective, nonpulsating tinnitus and its effect on tinnitus severity. The study included 201 tinnitus patients and 99 controls. Patient clinical information, including tinnitus characteristics and severity according to Tinnitus Handicap Inventory (THI), loudness assessed by Visual Analogue Scale (VAS), audiometry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Diet, specifically the Mediterranean one, could have a role in prevention of tinnitus onset and partly explain the relatively limited prevalence of tinnitus in areas of the Mediterranean basin [ 7 ]. This is confirmed by various researchers who postulated a potential protective influence of certain foods on tinnitus onset or annoyance [ 8 , 9 , 10 , 11 , 12 ], either Mediterranean food items (fresh fruit and vegetable intakes [ 10 ]) or other nutrients (reduced intake of vitamin B 2 and B 3 [ 8 ], chocolate intake [ 9 ], and improved intake of vitamin D [ 11 ] and manganese [ 12 ]), leading to preventive recommendations and, in some circumstances, even treatment recommendations, through dietary supplements. However, to date, there is no conclusive evidence to support the latter recommendations.…”
Section: Introductionsupporting
confidence: 67%
“…Diet, specifically the Mediterranean one, could have a role in prevention of tinnitus onset and partly explain the relatively limited prevalence of tinnitus in areas of the Mediterranean basin [ 7 ]. This is confirmed by various researchers who postulated a potential protective influence of certain foods on tinnitus onset or annoyance [ 8 , 9 , 10 , 11 , 12 ], either Mediterranean food items (fresh fruit and vegetable intakes [ 10 ]) or other nutrients (reduced intake of vitamin B 2 and B 3 [ 8 ], chocolate intake [ 9 ], and improved intake of vitamin D [ 11 ] and manganese [ 12 ]), leading to preventive recommendations and, in some circumstances, even treatment recommendations, through dietary supplements. However, to date, there is no conclusive evidence to support the latter recommendations.…”
Section: Introductionsupporting
confidence: 67%
“…In all three studies and four cohorts, the serum value of Vit D was found to be lower in patients with tinnitus than in those without, with WMDs ranging between −1.45 to −7.57 ng/mL. The pooled analysis performed using the quality effects models confirmed a significantly negative WMD of Vit D concentration in patients with tinnitus compared to those without, with a WMD of −6.2 ng/mL (95% CI, −10.3 to −2.1 ng/mL; I 2 , 56%), though such difference was largely determined by the study of Nowaczewska et al [ 18 ], expressing the largest sample size ( n = 300) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 77%
“…After excluding replicate publications among the three scientific search platforms, a total of 72 articles were originally detected using the predefined criteria and by hand-searching the reference lists, 69 of which ought to be eliminated because they did not present a comparison of serum Vit D levels in patients with or without tinnitus ( n = 29), did not assessed tinnitus ( n = 16) or Vit D status ( n = 5), lacked a control group of subjects without tinnitus ( n = 3), were review articles ( n = 11), editorial material ( n = 3) or case reports ( n = 2). A final number of 3 studies (all observational, case-control), with four cohorts and totaling 468 patients with ( n = 268) or without tinnitus ( n = 200) were finally included in our meta-analysis [ 16 , 17 , 18 ]. The main characteristics of these studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In all three studies and four cohorts, the serum value of Vit D was found to be lower in patients with tinnitus than in those without. The pooled analysis performed using the quality effects models confirmed a significantly negative WMD of Vit D concentration in patients with tinnitus compared to those without (WMD, -6.2 ng/mL; 95%CI, -10.3 to -2.1 ng/mL; I 2 , 56%)m, though such difference was largely determined by the study of Nowaczewska et al [18], expressing the largest sample size (n=300).…”
Section: Meta-analysismentioning
confidence: 83%
“…After excluding replicate publications among the three scientific search platforms, a total of 72 articles were originally detected using the predefined criteria and by handsearching the reference lists, 69 of which ought to be eliminated because they did not present a comparison of serum Vit D levels in patients with or without tinnitus (n=29), did not assessed tinnitus (n=16) or Vit D status (n=5), lacked a control group of subjects without tinnitus (n=3), were review articles (n=11), editorial material (n=3) or case reports (n=2). A final number of 3 studies (all observational, case-control), with four cohorts and totaling 468 patients with (n=268) or without tinnitus (n=200) were finally included in our meta-analysis [16][17][18]. The main characteristics of these studies are summarized in Table 1.…”
Section: Study Identification and Selectionmentioning
confidence: 99%